Assessment of water Quality Index of Gr oundwater in Al-Khadhimiya city - Abed Hussein, Tariq; Y. AL Kind, Ghayda; Hammoodi AL Ani, Faris (Iraqi Journal of Science, 2021)
The present study deals with the assessment of water Quality Index to theAl-Khadhimiya Groundwater city, by collection groundwater from 13wells during fourseasons, subjecting the samples to a comprehensive physicochemical analysis. The13 parameters have been considered: pH, total hardness, calcium, magnesium,turbidity, nitrate, electrical conductivity, total dissolved solid, Sulfate, Chloride,zinc, manganic, and iron, that are used for calculating the WQI. From the resultshown, the most groundwater quality lies in Unfit for human drinking purpose. Thewells (1 and 11) and wells (3 and 10) were a bad water quality for drinking purposesince they lie in poor and in very poor respectively according to the WQI. The primecauses of deterioration groundwater quality are turbidity, Hardness, Cl, SO4, Ca andMg.